Pancreatic response to secretion+CCK-PZ in European and North African adults and children. Issue 12 (December 1979) - Palasciano, G; Saunieres, J F; Laugier, R; Sarles, H
Abstract : Pancreatic response to intravenous secretin GIH (1CU/kg) +CCK-PZ (3CHRU/kg) was investigated in European and North African normal subjects. The pancreatic responses were compared in two groups of 38 normal male adults and in two groups of nine normal nurslings (less than 1 year). Body weight and age were similar in the two adult groups and in the two nursling groups. The peaks of volume, electrolytes, and enzymes were determined in samples of duodenal aspirate after hormonal stimulation. In adult subjects the flow rate and electrolytes were not statistically different in the two groups, while enzyme outputs were lower in the North African group -73% for lipase (P less than 0.001), -54% for phospholipase (P less than 0.01), and -35% for chymotrypsin (P less than 0.05). On the other hand, in both groups of nursling subjects all parameters of pancreatic secretion were identical. The difference in the pattern of the pancreatic response to exogenous hormonal stimulation observed between the two groups of adult subjects could be related to genetic or acquired differences. The second hypothesis is, however, the most probable because the pancreatic secretion was similar in both groups of nursling subjects.